Diamond Boron Nitride: Pressure‐Induced Formation and Mechanical Properties of 2D Diamond Boron Nitride (Adv. Sci. 2/2021) - Cellini, Filippo (Adv Sci (Weinh), 2021)
2D diamond boron nitride clusters are produced by inducing a sp(2) to sp(3) phase transition with the application of local pressure on atomically thin h‐BN on a SiO(2) substrate, at room temperature, and without chemical functionalization, as demonstrated in article number 2002541 by Elisa Riedo and co‐workers. Molecular dynamics simulations, mechanical measurements, and Raman spectroscopy experiments show a metastable local rearrangement of the h‐BN atoms into diamond crystal clusters, which depends on the applied pressure and number of atomic layers. [Image: see text]